STUDENTS’ PERCEPTION OF MEMORYLINGO APPLICATION ON VOCABULARY RECALLING ABILITY - Devi Manurung, Santi Sari; Ismahani, Siti (Universitas PGRI Sumatera Barat, 2025)
This study aims to understand students' perceptions towards the use of ‘MemoryLingo’ application in English vocabulary recall ability. This study employed a qualitative approach using a case study design. Purposive sampling was used to choose the participants, which included 20 eighth-grade students. This study's instruments included questionnaires and interviews. The questionnaire data were examined using descriptive statistics, while the interview data was analyzed thematically through coding to find recurring patterns and themes. The finding of this study indicated four major themes: (1) User Experience, (2) Vocabulary Retention Support, (3) Challenges in Using the Application, and (4) Overall Evaluation. As a result of the findings, it is possible to conclude that the majority of students found the MemoryLingo application to be enjoyable, interactive, and effective in helping them remember vocabulary.